News Framing of Low Immunization Coverage in Aceh: A Comparative Analysis of AJNN.net and Serambinews.com Coverage - Pahlewi, Mhd. Reza; Pawito, Pawito; Hastjarjo, Sri (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
Aceh is currently experiencing a public health crisis, with outbreaks of infectious diseases, including three cases of VDPV2 polio and a significant rise in diphtheria cases in 2023. Immunization plays a vital role in preventing and controlling diseases like polio and diphtheria. However, over the past five years, immunization coverage in Aceh has steadily declined, positioning it as the lowest in Indonesia. This study aims to explore how two local news outlets, Ajnn.net and Serambinews.com, frame news coverage regarding the low immunization rates in Aceh. Using a qualitative approach, the study applies Robert N. Entman’s framing analysis, which focuses on issue selection and salience. The findings reveal a notable difference in how the two media outlets frame the issue of low immunization coverage. Ajnn.net frames the issue by highlighting the root causes of the declining immunization rates, such as socio-economic factors and inadequate healthcare services. In contrast, Serambinews.com emphasizes the consequences of insufficient immunization, focusing on the potential health risks, outbreaks, and increased mortality rates among children. Despite their differing approaches, both outlets rely primarily on government sources for their reporting. This reliance makes their coverage less balanced and objective, as the perspectives of other stakeholders, such as local health experts, parents, and community organizations, are largely excluded. The analysis suggests that while Ajnn.net sheds light on the underlying causes of low immunization rates, Serambinews.com underscores the dire consequences. Both outlets, however, could enhance their reporting by incorporating a wider range of sources to offer a more comprehensive and investigative view of the issue.